Anti-inflammatory Activity of Ipomoea batatas Leaves Ethanolic Extract Tablet with Variation of Polyvinylpyrrolidone and Amylum Binders - Pramiastuti, Oktariani; Rizqi, Muhammad Irsan; Nurhidayati, Lailiana Garna; Firsty, Girly Risma (Jurnal Jamu Indonesia, 2025)
Purple sweet potato (Ipomoea batatas (L.) Lam.) leaves are traditionally used as an anti-inflammatory remedy. This study investigated the anti-inflammatory activity of purple sweet potato leaf ethanolic extract and its formulation into tablet dosage forms with varying concentrations of polyvinylpyrrolidone and amylum as binders. The extract was obtained through maceration using 96% ethanol and tested for anti-inflammatory activity using the bovine serum albumin denaturation method. The extract showed strong anti-inflammatory activity with an IC₅₀ value of 62.628 ppm compared to sodium diclofenac with an IC₅₀ of 57.326 ppm. The extract was then formulated into tablets with binder ratios of 1:0, 0:1, 1:1, 2:3, and 1:4 (polyvinylpyrrolidone: amylum) using wet granulation. Evaluation of physical properties indicated that the 1:1 binder ratio produced tablets that met quality requirements, including hardness, friability, and disintegration time. These results suggest that I. batatas leaf extract has potent anti-inflammatory properties and is suitable for development into a tablet formulation with appropriate binder ratios.